Decarbonization, Environmental Regulation, and Economic Boom: An Indicator Assessment Based on the Industrial Waste - Yang, Liu; Ma, Zhili; Ma, Minda; Xu, Yang (Frontiers in Energy Research, 2022)
Energy-based economic development brings about some environmental problems, and as China’s economy shifts from rapid growth to high-quality development, the implementation of environmental regulation is crucial to achieving environmental protection and high-quality economic development. Based on the panel data of 14 prefectures and cities from 2000 to 2018 in Xinjiang, this study explored the impact of environmental regulation on high-quality economic development by constructing a comprehensive evaluation index system and using entropy method and Tobit regression model. The results show that 1) overall, each 1% increase in environmental regulation is associated with a 0.037% rise in high-quality economic development level; 2) regionally, each 1% increase in environmental regulation is associated with a 0.119% rise in high-quality economic development level in northern Xinjiang, but the effect on the southern Xinjiang is not significant; 3) each 1% increase in environmental regulation, the level of high-quality economic development decreased by 0.034% from 2000 to 2010 and increased by 0.061% from 2011 to 2018. In general, this study adds to the theoretical and empirical study on the influence of environmental regulation on high-quality economic development while providing a methodology for other economies to assess the relationship between the two.